Bacterioplankton seasonality in deep high-mountain lakes - Zufiaurre, Aitziber; Felip, Marisol; Camarero, Lluís; Sala-Faig, Marc; Juhanson, Jaanis; Bonilla-Rosso, German; Hallin, Sara; Catalan, Jordi (Frontiers in Microbiology, 2022)
Due to global warming, shorter ice cover duration might drastically affect the ecology of lakes currently undergoing seasonal surface freezing. High-mountain lakes show snow-rich ice covers that determine contrasting conditions between ice-off and ice-on periods. We characterized the bacterioplankton seasonality in a deep high-mountain lake ice-covered for half a year. The lake shows a rich core bacterioplankton community consisting of three components: (i) an assemblage stable throughout the year, dominated by Actinobacteria, resistant to all environmental conditions; (ii) an ice-on-resilient assemblage dominating during the ice-covered period, which is more diverse than the other components and includes a high abundance of Verrucomicrobia; the deep hypolimnion constitutes a refuge for many of the typical under-ice taxa, many of which recover quickly during autumn mixing; and (iii) an ice-off-resilient assemblage, which members peak in summer in epilimnetic waters when the rest decline, characterized by a dominance of Flavobacterium, and Limnohabitans. The rich core community and low random elements compared to other relatively small cold lakes can be attributed to its simple hydrological network in a poorly-vegetated catchment, the long water-residence time (ca. 4 years), and the long ice-cover duration; features common to many headwater deep high-mountain lakes.